2019
DOI: 10.1088/1361-6595/ab252d
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of electron density and temperature in low pressure transient Ar/N2 plasmas estimated by optical emission spectroscopy

Abstract: A recently published method for the analysis of phase-resolved optical emission spectra was extended in order to permit estimation of time-resolved electron density profiles. The previously presented method combined collisional-radiative modelling with a self-absorption method to estimate the evolution of T e with sub-cycle time-resolution. However, it was not capable to give similar profiles for n e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…A significant drop of an order of magnitude in 1s state densities was observed when nitrogen concentration was increased up to 50 sccm. Similar behavior was observed in previous work [14] based purely on optical emission measurements and collisionalradiative modeling. Precise modeling of 2p 8 state requires the description of one more transition branch 2p 8 → 1s 2 at 978.45 nm.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A significant drop of an order of magnitude in 1s state densities was observed when nitrogen concentration was increased up to 50 sccm. Similar behavior was observed in previous work [14] based purely on optical emission measurements and collisionalradiative modeling. Precise modeling of 2p 8 state requires the description of one more transition branch 2p 8 → 1s 2 at 978.45 nm.…”
Section: Resultssupporting
confidence: 87%
“…The quenching rate is given as product of species density n and deactivation rate constant k q , reported in [11] for k q,Ar , [12] for k q,N 2 and [13] for k q,e . The electron density for argon admixture with nitrogen was expected to be in order of few 10 16 m −3 comparable to measured values in [14] for unmagnetized plasma and similar conditions. If the laser frequency matches the transition frequency 1s 4,m j → 2p 8,m i , the sub-level is pumped and its density can be obtained by…”
Section: Tunable Diode Laser Induced Fluorescence In Magnetized Plasmasupporting
confidence: 81%
“…Phase dependent development of plasma produced in same configuration and similar conditions has been investigated in previous works [12,24] where strong variations in plasma parameters as well as in 1s state densities were observed. Plasma dynamics under the conditions investigated here illustrated by phase resolved emission of 842.47 nm argon line is shown in figure 4.…”
Section: Resultsmentioning
confidence: 78%
“…Emission spectra of an argon low temperature plasma have been successfully analysed by modelling collisional and radiative processes responsible for the population of excited states [43,44]. In the complete model for argon [44,45] the populations of the first 14 excited states (Ar(1s) and Ar(2p) branches) were modelled including electron impact excitation from ground state, electron coupling between and within the Ar(1s) and Ar(2p) levels, and electron quenching and radiative processes including light trapping. It was shown that in the case of low temperature plasmas with moderate electron densities and temperatures, the collisional-radiative model (CRM) can be simplified to an extended corona model including excitation from ground and 1s states and radiation transfer processes [44,46].…”
Section: B Collisional Radiative Model Of An Argon Discharge Containing Aluminiummentioning
confidence: 99%